Internal audit of spending units and its impact on the efficiency of the federal budget (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The role of internal control is based on the effectiveness of the budget through an analysis of the reality of the budget in the research sample as it was studied in the preparation and preparation stages and the implementation stage. The sample showed that the sample did not comply with what is stated in the Ministry of Finance publication of instructions and ceilings. In the process of preparing and resulting from the occurrence of deviations in large proportions both in the discussion of the Ministry of Finance or when implementation as a low rate of implementation and the absence of allocations for some items, although there is a need for them as well as the transfer of large proportions of transfers both up or down and the purpose of the research to highlight the role Which is played by the internal audit and the reflection of this role on the effectiveness of the budget through the stages of the budget resulting in positive results in the implementation of the most important conclusions lack of a role of internal control in the process of preparation and preparation, despite the text of the Ministry of Finance on the contribution of the Internal Audit Department and the rest of the sections concerned and not The most important recommendations were the need to adopt standards and scientific or practical foundations when preparing budget estimates, increasing the independence of internal control and expanding its activity, and not limited to routine work to cover all events. Including participation in the preparation and audit of budget estimates.